Empowering Mothers: Relatianship of Toddler Mother Class Participation on Maternal Knowledge of Toddler Nutrition in Karangjati Village - Nadia Oktaviana; Vistra Veftisia; Yulia Nur Khayati (Universitas Ngudi waluyo, 2026)
The issue of toddler nutrition requires special attention based on the results of the 2022 Indonesian Nutritional Status Survey (SSGI), the prevalence of malnutrition in toddlers in Indonesia increased to 17.1%. Meanwhile, the Semarang Regency Health Office in 2023 the number of toddlers with cases of malnutrition increased to 3,878 toddlers (6.6%). At the Bergas Community Health Center, there were 81 toddlers experiencing malnutrition. From the results of a preliminary study of 5 respondents, 3 mothers who actively participated in the class for mothers of toddlers, 2 mothers were able to explain all indicators of nutritional status. Where 1 other mother who also attended the class did not fully understand the indicators of nutritional status. the aim of the research is to find out Meanwhile, the two mothers who did not attend the class showed varying results, where one of them only knew weight as an indicator and the other actually knew about nutritional status and how to monitor nutritional status. research purposes ti findRelationship Of Toddler Mother Class Participation On Maternal Knowledge Of Toddler Nutrition This study used a correlational analytical design. The population in this study was 582 respondents. The sample in this study was 85 respondents, determined using the Slovin formula approach with a 10% error rate. This determination was carried out to obtain a representative sample of the population. The sampling technique used was accidental sampling, and a questionnaire was used as the data collection tool. The analysis test used the chi-square test. Most respondents were not actively participating in the mother and toddler class, amounting to 43 respondents (50.6%). Most respondents had good knowledge, amounting to 54 respondents (63.5%). The results of the chi-square test with a degree of error of α = 0.05 obtained a p-value of 0.000 <α = 0.05. Conclusion: There is a relationship between mothers' participation in toddler mother classes and knowledge about toddler nutrition